The participatory market chain approach: stimulating pro-poor market-chain innovation - Bernet, T.; Devaux, A.; Thiele, Graham; López, G.; Velasco, C.; Manrique, K.; Ordinola, M. (2008)
Innovation in the food and agriculture sector is frequently short-circuited by a lack of trust and communication between actors in the market chain. To overcome these problems and stimulate innovation, the Participatory Market Chain Approach (PMCA) brings together small farmers, market agents, and service providers for an intense process of facilitated interaction. The PMCA uses a flexible three-stage participatory process to improve communication, build trust, and facilitate collaboration among participants so that they can jointly identify, analyze, and exploit new market opportunities. The PMCA focuses on innovation in products, technologies, and ways of working together. By carefully selecting market chains and partners, and building in social responsibility, the PMCA can lead to favourable outcomes and impacts for poor farmers, typically the weakest link in the chain. The PMCA requires facilitation and technical support from professionals with good social skills, research experience, and marketing knowledge, based in a neutral research and development organization. To ensure that impacts are sustained, the PMCA is best used as part of a broader programme of market chain development.